Mitochondrial DNA copy number in peripheral blood cells declines with age and is associated with general health among elderly - Mengel-From, Jonas (2014)
The role of the mitochondria in disease, general health and aging has drawn much attention over the years. Several attemptshave been made to describe how the numbersof mitochondriacorrelate with age, although with inconclusive results. In this study, the relativequantity of mitochondrial DNA compared to nuclear DNA,i.e. the mitochondrial DNA copy number, was measured by PCR technology and used as a proxy for the content of mitochondria copies. In 1,067 Danish twins and singletons (18-93 years of age), with the majority being elderly individuals, theestimated mean mitochondrial DNA copy numberin peripheral blood cells was similar for those 18-48 years of age (mean relative mtDNA content: 61.0; 95% CI [52.1; 69.9]), but declinedby −0.54 mtDNA 95%CI [−0.63; −0.45] every year for those older thanapproximately 50 years of age.However, the longitudinal, yearly decline within an individual was more than twice as steep as observed in the cross-sectional analysis (decline of mtDNA content: −1.27; 95%CI [−1.71; −0.82]). Subjects with low mitochondrial DNA copy numberhad poorer outcomes in terms of cognitive performance, physical strength, self-rated health, andhigher all-cause mortality than subjects with high mitochondrial DNA copy number, also when age was controlled for.The copy numbermortality associationcan contribute to the smaller decline in a cross-sectional sample of the population compared to the individual,longitudinal decline. This study suggests that high mitochondrial DNA copy number in blood is associated with betterhealth and survival among elderly.